Feses Kuda Sebagai Sumber Mikrobia Pengganti Cairan Rumen Dalam Analisis Kecernaan In Vitro Pada Pakan Berserat Rendah - SABILA, Absharina Nur ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aims to know the difference of rumen fluid, cattle feces, and horse’s feces as source of microbes to substitute rumen fluid in an analysis of in vitro digestibility of low fiber feed. The research applies in vitro method generated by Tilley and Terry in two stages that was modified by Utomo. Feed used in the research were corn, rice bran, dried cassava, coconut meal, soy bean meal, and pangola grass. Feed digestibility was tested using different microbes sources of rumen fluid, cattle feces, and horse’s feces. Each feed was used repeatedly 3 times for each source of microbes. The research used randomized complete block design (RCBD) continued by Duncan’s new multiple range test (DMRT). Observed variables of this in vitro digestibility of dry matter and organic matter. The result of the research showed that the average of in vitro digestibility of dry matter and organic matter on stage I and stage II are significantly different in each treatment. Digestibility of dry matter in stage I of using rumen fluid, cattle feces, and horse’s feces as microbes source were 64.83%; 53.13%; 52.40% while organic matter digestibility were 57.03%; 46.18%; 47.68%. Digestibility of dry matter in stage II of rumen fluid, cattle feces, and horse’s feces were 72.99%; 67.41%; 66.25% while organic matter digestibility were 66.98%; 60.71%; 59.12%. The use of horse’s feces as source of microbes to substitute rumen fluid didn’t show much different result than cattle feces. Digestibility patterns between rumen fluid, cattle feces, and horse’s feces were different so using horse’s feces as source of microbes could not substitute rumen fluid. Key words: In vitro digestibility, Rumen fluid, Cattle feces, Horse feces, Low fiber feed